(untitled) (DAPesquisa, 2021)
This article aims to identify action of aesthetic-politic engagement of Zkaya a South Brazilian brand turn to enrich subjectivities of black identities in the context of activism and Afro-Brazilian fashion contemporary scenario. It is a basic research, qualitative and descriptive, whose bibliographic research allowed to build the treoretical basis, who debate at first on how the power structures operate over the [black] body, how the fashion has a fundamental role on its “docilization” and, nevertheless, point to the fact that where resides power, resides resistence; In the following, shows a comparative of how Brazilian activist brands are defying the dominant system, to finally presente the results of collected data though interviews, brand’s website and social media, so as to make possible the affirmation that Zkaya is an activist brand that gives new meaning to fashion and values the social-cultural and historical aspects associated to subjectivities of black identities.